Review of the clinical status of cardiotoxicity of HER-2 positive breast cancer targeted therapeutic drugs - Zhang, Xiang; Yin, Yulian; Yu, Qiuting; Chen, Xinlin; Cheng, Yiqin (Frontiers in Oncology, 2025)
Breast cancer is a major health challenge for women worldwide, and human epidermal growth factor receptor 2 (HER-2)-positive breast cancers have a relatively high incidence and are highly aggressive. Targeted therapeutic agents, represented by trastuzumab, have been effective in improving the survival rate of HER-2-positive breast cancer patients. However, in clinical applications, this type of targeted drugs exhibits varying degrees of cardiotoxicity, and the mechanism of their cardiotoxicity is currently unclear. In this paper, we classify them into three categories: monoclonal antibodies (mAbs), small-molecule tyrosine kinase inhibitors (TKIs), and antibody-drug conjugate (ADCs). We list the evidence of cardiotoxicity for various drugs based on current clinical trials and summarize their corresponding epidemiological profiles. We also discuss the regulation of cardiotoxicity from three perspectives: clinical biomarkers of cardiotoxicity, permissive cardiotoxicity, and the current status of cardiotoxicity regulation.